2015
DOI: 10.1152/ajpcell.00375.2014
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling AMPK from autophagy: a foe that hinders the beneficial effects of metformin treatment on metabolic syndrome-associated atherosclerosis? Focus on “Glucose and palmitate uncouple AMPK from autophagy in human aortic endothelial cells”

Abstract: METABOLIC SYNDROME IS A CLUSTER of conditions including insulin resistance, dyslipidemia, hypertension, and central obesity, and it results in an increased risk of type 2 diabetes mellitus and cardiovascular diseases such as atherosclerosis. These conditions are rising year to year and are a leading cause of deaths worldwide. Therefore, potential therapeutic approaches to attenuate the pathogenesis of metabolic syndrome are urgently needed. Autophagy is a bulk intracellular degradation pathway that involves th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…Previous studies have suggested that metformin exerts significant cardioprotective effects alongside its fundamental role as an antidiabetic agent ( 10 , 11 ). The mechanism of action of metformin in atherosclerosis is associated with AMPK ( 29 , 30 ). It has previously been reported that numerous cytokines, chemokines and growth factors regulate smooth muscle cell proliferation and the progression of atherosclerosis ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that metformin exerts significant cardioprotective effects alongside its fundamental role as an antidiabetic agent ( 10 , 11 ). The mechanism of action of metformin in atherosclerosis is associated with AMPK ( 29 , 30 ). It has previously been reported that numerous cytokines, chemokines and growth factors regulate smooth muscle cell proliferation and the progression of atherosclerosis ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Upon injury, endothelial cell autophagy may occur to protect the cells from being damaged, while the failure or inhibition of autophagy results in endothelial cell apoptosis, leading to the break-down of the integrity of endothelium to facilitate the local lipid deposition into atherogenesis, plaque instability, and even acute coronary occlusion and sudden death [13,[18][19][20][21][22][23]. Nevertheless, our understanding of the mechanisms that control the autophagy of endothelial cells is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy-associated protein 6 (ATG6, or Beclin-1), ATG7 and p62 are several key autophagy-associated proteins that strongly induce autophagy in an independent or coordinated manner [27]. Autophagy has been shown to play a critical role in endothelial cells to prevent development of atherosclerosis [13,[18][19][20][21][22][23]. Nevertheless, the underlying mechanisms remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the autophagosome formation is dependent on the AMPK, due to direct phosphorylation of VPS34 and BECN1, and then regulates the activity of BECN1 complex (Kim et al, 2013). Taken together, when cellular energy is depleted, AMPK can regulate mTOR, ULK1, and VPS34-BECN1 complex and then guarantee the activation of autophagy (Ding, 2015). In VSMCs, TRPV1 induced by capsaicin can activate autophagy and then decrease the accumulation of lipid through decreased uptake of lipid and promote cholesterol efflux.…”
Section: Vsmc Autophagy In Atherosclerosismentioning
confidence: 99%